The analysis of policy implementation models in higher education: the case study of Indonesia. (2nd January 2019) - Gaus, Nurdiana; Yunus, Muhammad; Karim, Abdul; Sadia, Haleema
ABSTRACT: This paper aims to analyse and understand the models of policy implementation in Indonesian state universities during the ongoing process of market-driven reforms and how academics respond to these models. The research undertaken was in the form of qualitative study using semi-structured interviews as instruments to collect data. Interviews were conducted with 30 academics in three state universities in Indonesia. The research demonstrated that policy implementation in Indonesian state universities takes largely a dialectical form which takes place both at macro and micro levels, suggesting a blended application of top-down and bottom-up approaches. The results of this study also confirmed that the interaction between policy and local systems plays an important role for the successful implementation of the policy. Indonesian academics perceived that each of these models has its strength and weaknesses particularly in relation to the aspect of collegiality. It is anticipated that the study will both contribute to a better understanding of the dynamics between governments as policy makers and academics as street level bureaucrats in the implementation of a policy, and offer guidance for policy makers in the formulation and enactment of relevant policies in higher education sectors both in Indonesia and other contexts implementing policy implementation.